Some remarks on the original price index inspired by the notes of Peter von der Lippe - Białek, Jacek (Pewne uwagi o autorskim indeksie cen, zainspirowane notatkami Petera von der Lippego, 2013)
We discuss an original price index formula presented in Białek [2012a] and Białek [2012b]. The inspiration for this discussion are the correlated notes of Prof. Peter von der Lippe. This article presents the author’s point of view on the problems considered by Prof. Peter von der Lippe and some other properties of the discussed formula
Ekonometria = Econometrics, 2013, Nr 3 (41), s. 40-54
Keywords: price index; generalized price index; Laspeyres index; Paasche's index; Fisher's index; Białek's index; indeks cen; uogólniony indeks cen; indeks Laspeyrsa; indeks Paaschego; indeks Fishera; indeks Białka